Studies of expression and localization of endogenous G-protein subunits using bioluminescence imaging - Kuchynka, Ondřej (Jihočeská univerzita, 2023)
G-protein subunit subtypes play an important role in the regulation of G-protein signaling, which is linked to numerous diseases from schizophrenia to cancer. Aside from the widely explored G-alpha subunits, G-gamma subunit subtypes are also known to exhibit specific attributes like vastly different membrane affinity and varying expression levels. Here we set out to ascertain the effect of those specific attributes on the dynamic properties of four different G-protein subunits using bioluminescence imaging. An important part of our study is the focus on displaying G-proteins in an endogenous setting with unaltered expression levels. The aim of this research is to study the endogenous localization, in some subunits yet unknown, while also comparing the endogenous expression levels of the four subunits. In doing so, we also hope to explore the possibilities of bioluminescence imaging in the context of protein visualization.
Studies of expression and localization of endogenous G-protein subunits using bioluminescence imaging
Keywords: G-protein; G protein-coupled receptor; signaling; localization; expression; bioluminescence imaging; G-protein; G protein-coupled receptor; signaling; localization; expression; bioluminescence imaging